Per una nuova edizione critica delle Antiquitates rerum humanarum di Varrone - Lucarini, Carlo M. (Hyperboreus, 2023)
The aim of this paper is to support my reconstruction of the Antiquitates rerum humanarum of Varro oﬀered in the forthcoming Teubner edition, Geographi veteres vel minores vel quorum fragmenta exstant. The last edition of this work was published by P. Mirsch in 1882 and was aﬀected by several misconceptions and omissions. One of my eﬀorts is to show that Censorinus’ De die natali is an invaluable aid in reconstructing the structure of the books 14–19 of the Antiquitates rer. hum., since Censorinus structured the last part of his work on Varro’s model. Also the dependence on Varro of Plinius’s Nat. hist. (especially in the geographical books) and of Dionysius’ Antiquitates Romanae is studied.